Forward, Forward Option and No Hedging Which One is the Best for Managing Currency Risk? - Riko Hendrawan (University of Merdeka Malang, 2017)
Bank Indonesia Regulation No.18/18/PBI/2016 concerning foreign exchange transactions against rupiah between banks and domestic parties, indicates that the importance of hedging for business actors in Indonesia. Based on the data of the rupiah exchange rate movements against the dollar from January 2006 to December 2016 shows that the fluctuation of the rupiah against the US dollar tends to weaken, although at some point the observation shows the strengthening of the rupiah against the US dollar. The purpose of this research is to assess the impact of forward, Forward Option and No Hedging Strategy for managing currency exposure between IDR to USD. Using data from January 2006–December 2016 taken from the website of Bank Indonesia and Federal Reserve. Total 396 simulations, consists of 132 using Forward simulations, 132 using Forward Option simulations and 132using No Hedging simulations. Findings from this research show that Forward Option was has no positive contribution in managing currency exposure, No Hedging Strategy has 36,36 percent positive contribution and the forward contract has 72,73 percent positive contribution in managing currency exposure. Its means Forward Contract was better than forward Option and No Hedging Strategies in managing currency exposure.DOI: https://doi.org/10.26905/jkdp.v21i3.1428